Retrosigmoid Suprameatal Approach for Resection of Petrotentorial Cerebellopontine Angle Meningioma: Operative Video and Technical Nuances - Liu, James K.; Dodson, Vincent N. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Meningiomas are the second most common tumor to arise in the cerebellopontine angle. In this operative video atlas manuscript, the authors demonstrate a step-by-step technique for microsurgical resection of a petrotentorial meningioma in the cerebellopontine angle via a retrosigmoid suprameatal approach. Drilling of the hyperostotic suprameatal tubercle was necessary to gain access to the dural origin and anterior petrosal extent of the tumor. The nuances of microsurgical and skull base technique are illustrated including microsurgical dissection of the tumor away from the brainstem and neurovascular structures, facial nerve preservation, and fat graft-assisted Medpor Titan reconstruction to prevent cerebrospinal fluid leakage. A gross total resection was achieved, and the patient was neurologically intact. In summary, the retrosigmoid suprameatal approach is an important strategy in the armamentarium for surgical management of petrotentorial meningiomas in the cerebellopontine angle.The link to the video can be found at: https://youtu.be/kwQP6BSYK7U.
Keywords: retrosigmoid; suprameatal; petrotentorial; cerebellopontine angle; meningioma; microsurgery